N-(3-Chlorophenyl)benzenesulfonamide - Gowda, B. Thimme (International Union of Crystallography, 2008)
In the crystal structure of the title compound, C(12)H(10)ClNO(2)S, the N—H bond is trans to one of the S=O bonds. The two aromatic rings form a dihedral angle of 65.4 (1)°, compared with a value of 49.1 (1)° in N-(2-chlorophenyl)-benzenesulfonamide. The molecules are connected by intermolecular N—H⋯O hydrogen bonds into chains running along the b axis.